Knowledge and attitude of dental undergraduates, graduates, and postgraduates on dental implants for children – A cross-sectional study - Ramya Ramanathan; Paul Chalakkal; Ridhima Gaunkar; Vidya Baliga (Journal of Indian Society of Pedodontics and Preventive Dentistry)
Context: Dental implants for children are a new treatment modality. Dental implants in children restore function, preserve the alveolar bone, and give excellent esthetics, restoring the child’s confidence and social acceptability. Aim: Knowledge and attitude toward dental implants for children among dental undergraduates, graduates, and postgraduates. Settings and Design: This was a cross-sectional web-based questionnaire study. Methodology: The Google Form link was circulated among various social media platforms. The responses were obtained through Google Forms. This survey focused on demographic data-, knowledge-, and attitude-based questions. Statistical Analysis: The data obtained was compiled into a Microsoft Excel document and the analysis was done using IBM SPSS for Windows version 24.0 (IBM Corp., Armonk, USA). Chi-square test was used to compare the responses based on educational qualification and clinical experience among study participants. Kruskal–Wallis followed by Dunn’s post hoc test was used to assess mean knowledge scores across different educational qualification groups. Mann–Whitney test was used for the comparison of mean knowledge scores among the categories of clinical experience. Results: The undergraduates had more knowledge scores compared to graduates and postgraduates. The mean knowledge scores showed a significant difference based on the clinical experience of the study participants. Knowledge score was higher in participants who had clinical experience of <2 years. Conclusion: Undergraduates and those with less than 2 years of clinical experience were found to have greater knowledge scores regarding the use of dental implants in children.